2019
DOI: 10.1063/1.5085502
|View full text |Cite
|
Sign up to set email alerts
|

Local structure origin of ultrafast crystallization driven by high-fidelity octahedral clusters in amorphous Sc0.2Sb2Te3

Abstract: Phase-change material Sc0.2Sb2Te3 (SST) can remarkably boost the writing speed of memory devices due to the extremely fast crystallization. It was demonstrated that the fast crystallization is because Sc stabilizes the 4-fold rings which act as precursors of nuclei in the amorphous phase. In this work, by using first-principles molecular dynamics simulations, we studied the local structures in the liquid and amorphous SST at various temperatures. The results reveal that Sc-centered configurations are almost in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…There are almost no tetrahedrons in the Bi 2 Te 3 or Sb 2 Te 3 systems at 300 K. For Te-centered clusters of amorphous Bi 2 Te 3 , the proportion of 6-fold perfect octahedron is very small, there are mainly defective octahedrons with 3-, 4-, 5-fold octahedrons, resulting in the non-uniform volume of central and surrounding spheres appears in collective alignments result of Te-centered clusters at 300 K (figure 3). By comparison, we find that most of the distorted octahedral clusters in the Bi 2 Te 3 glass sample exist in the Bicentered configuration, and the SRO in Bi 2 Te 3 is stronger than that in the Sb 2 Te 3 system at 300 K. Introducing a small amount of Sc alloy into Sb 2 Te 3 could significantly enhance the crystallization speed at elevated temperatures [13], and Qiao et al [29] found that Sc forms much more robust octahedral motifs than Sb and Te, which significantly and clearly reduces the stochasticity of nucleation. Therefore, the stable octahedral structure in amorphous state could be regarded as a crystal seed to enhance crystallization speed.…”
Section: Resultsmentioning
confidence: 68%
“…There are almost no tetrahedrons in the Bi 2 Te 3 or Sb 2 Te 3 systems at 300 K. For Te-centered clusters of amorphous Bi 2 Te 3 , the proportion of 6-fold perfect octahedron is very small, there are mainly defective octahedrons with 3-, 4-, 5-fold octahedrons, resulting in the non-uniform volume of central and surrounding spheres appears in collective alignments result of Te-centered clusters at 300 K (figure 3). By comparison, we find that most of the distorted octahedral clusters in the Bi 2 Te 3 glass sample exist in the Bicentered configuration, and the SRO in Bi 2 Te 3 is stronger than that in the Sb 2 Te 3 system at 300 K. Introducing a small amount of Sc alloy into Sb 2 Te 3 could significantly enhance the crystallization speed at elevated temperatures [13], and Qiao et al [29] found that Sc forms much more robust octahedral motifs than Sb and Te, which significantly and clearly reduces the stochasticity of nucleation. Therefore, the stable octahedral structure in amorphous state could be regarded as a crystal seed to enhance crystallization speed.…”
Section: Resultsmentioning
confidence: 68%
“…[57,114] As indicated in Figure 4b, the ab initio molecular dynamics simulations revealed that the four-fold atomic rings are the precursors of the nuclei, [117] and stabilizing these crystal seeds could remarkably boost the crystallization speed. [118] For the growth-dominated PCMs, the crystallization speed can be controlled by changing the activation energy of the diffusion and the mobility of atoms. For example, adding C dopants could slow down the growth, [59] so that different crystallinity can be achieved in neuromorphic devices.…”
Section: Transition Dynamicsmentioning
confidence: 99%
“…Ab initio materials screening studies have recently shown that alloying with a suitable element, such as Sc [10][11][12][13][14][15] or Y [16][17][18][19] , can largely increase the nucleation rate to improve switching speed at elevated temperatures. The recently designed Sc 0.2 Sb 2 Te 3 (SST) alloy brings the programming time down to~0.7 ns, expanding the capability of PRAM for cache-type memory applications [10][11][12][13][14][15] . The stability of amorphous Sb 2 Te 3 thin films can also be improved by alloying with Sc, leading to a T x of about 150°C-due to an increase in viscosity, and thus a decrease in growth rate, at low temperatures [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%